컨텐츠 전송을 위한 브로커 시스템 구조에 관한 연구 - Simalango, Mikael Fernandus (The Graduate School, Ajou University, 2010)
In today’s internet, we face the redundancy of contents due to the rise of social web. Redundant contents which only sit on content provider infrastructure without being accessed frequently may not bring immediate problem. However, some portals can have interests on such contents and may take benefit of them by collaborating with the content providers instead of building their own infrastructure to host and provision the contents. Content redundancy can also be visited from the emergence of cloud computing. With the inceptions of Infrastructure as a Service (IaaS) providers, contents can be hosted on infrastructure leased by the providers economically and content provisioning is to be executed by selecting from one of the providers based on certain criteria. This thesis proposes an architectural design for collaborative content delivery system to address this issue. This architecture enables contents to be fed from several content providers and snapshots of them made available on a portal that acts as the content broker. The broker in this architecture mediates every content request and delegates provisioning of the content to a content provider out of several candidates that can meet user’s required QoS level. Provider selection scheme is built on top of provider ranking system. The ranking system makes use of periodic QoS measures of providers’ networks to estimate reliability of providers in circumventing failure of QoS provisioning during a content delivery transaction. A fairness model is also introduced thus approach in the offered model is expected to bring this design to be attractive to nowadays’ content delivery regime. The simulation results show that using fair provider selection and applying load balance principle, contents can be provisioned by better pool of qualified providers thus allowing QoS levels to be expectedly satisfied in accordance with user requirements.
학위논문(석사)--아주대학교 일반대학원 :컴퓨터공학과,2010. 2
Keywords: content delivery; brokering system; architectural design; distributed computing; 컨텐츠 전송; 브로커 시스템 구조